Pengaruh Edukasi terhadap Dukungan Keluarga dalam Pengelolaan Hipertensi pada Lansia di UPTD Puskesmas Jekan Raya, Palangka Raya - Naniek Sukesie; Karmitasari Yanra Katimenta; Meilitha Carolina; Septian Mugi Rahayu (Jurnal Siti Rufaidah, 2024)
Education is an independent nursing intervention designed to help individuals, groups, or communities, including hypertension patients, address their health issues through learning activities, with nurses acting as educators. Hypertension is a chronic disease often referred to as the "silent killer." Family support is crucial for hypertension patients in dealing with problems that arise during long-term treatment. Based on interviews with 10 elderly hypertension patients, it was found that when they went for health check-ups and monitoring at healthcare facilities, they were not accompanied by their families. This study aims to analyze the Effect of Education on Family Support in Hypertension Management for the Elderly at UPTD Jekan Raya Health Center, Palangka Raya. Method: This study used a Pre-Experimental Design with a One-Group Pretest-Posttest approach. The sampling technique was Purposive Sampling, with 49 respondents. Results: Based on the results of the Paired Sample Test, a p-value of 0.00 was obtained, which indicates a significance level of p < 0.05. Therefore, it can be concluded that the alternative hypothesis (Ha) is accepted, meaning that education significantly influences family support in managing hypertension in the elderly at UPTD Jekan Raya Health Center, Palangka Raya. Conclusion: There is a significant effect of education on family support in managing hypertension for the elderly at UPTD Jekan Raya Health Center, Palangka Raya.